SISTEM INFORMASI PEMBERIAN BONUS INSENTIF KARYAWAN MENGGUNAKAN METODE AHP DENGAN MEKANISME PEMBOBOTAN KRITERIA TERSTRUKTUR PADA XYZ - Edy Siswanto (Informatika: Jurnal Teknik Informatika dan Multimedia, 2026)
Bonus incentives are additional rewards provided to employees to improve motivation, productivity, and work performance. PT. XYZ faces difficulties in determining eligible bonus recipients because the assessment process involves multiple criteria and is still conducted conventionally using Microsoft Excel. The manual process requires data collection, sorting, calculation, and reporting, which takes considerable time and often results in less accurate decisions due to subjective judgment. To address this issue, this research implemented a Decision Support System using the Analytical Hierarchy Process (AHP) method. The developed system helps simplify and accelerate the evaluation process in determining employees who deserve bonus incentives more objectively and accurately. In addition, the system is capable of generating decision reports quickly, securely, and in a structured manner, thereby improving efficiency and supporting better decision-making within the company.